2017
DOI: 10.1155/2017/2084256
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Composition of Mangrove Associations in Tubli Bay of Bahrain as Affected by Municipal Wastewater Discharge and Anthropogenic Sedimentation

Abstract: The effects of municipal wastewater discharge and anthropogenic sedimentation on the structure and composition of gray mangrove (Avicennia marina (Forsk.) Vierh.) communities along Tubli Bay coastlines in Bahrain were investigated. Growth and regeneration of mangrove were measured, and its community was characterized. Sediment profile was analyzed for texture, pH, and salinity. Mangrove area covered by sand depositions was measured using Google Earth Pro. ANOVA and regression tests were employed in the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This may also be suggestive of the resultant effect of the certain prevailing factors culminating in the alteration of major aspects of the environment. Seedo et al (2017) confirmed this by noting that an understanding of the functionality of location specific factors were as important as other already generally established factors. Some of which could be the fauna, tidal regime and other environmental conditions.…”
Section: Resultsmentioning
confidence: 64%
“…This may also be suggestive of the resultant effect of the certain prevailing factors culminating in the alteration of major aspects of the environment. Seedo et al (2017) confirmed this by noting that an understanding of the functionality of location specific factors were as important as other already generally established factors. Some of which could be the fauna, tidal regime and other environmental conditions.…”
Section: Resultsmentioning
confidence: 64%